Comparative mid-term evaluation of unilateral and bilateral total knee arthroplasty utilizing metal-backed components: An assessment of functional and clinical outcomes - Ponnanna Karineravanda Machaiah; Supreet Bajwa; Ravi Teja Rudraraju; Kunal Aneja; Haresh P. Bhalodiya; Rakesh Kumar Singh; Vividh Makwana; Avtar Singh; Vivek Logani; Buddhadev Chatterjee; Devendra S. Solanki; Hemant Wakankar; et al. (Journal of Orthopaedic Reports)
Objective: This prospective, post-marketing surveillance (PMS) study (Freedom 400) aimed to evaluate the clinical and functional outcomes of both unilateral and bilateral total knee arthroplasty (TKA) utilizing cruciate retaining/posterior stabilized (CR/PS) implants with metal-backed components (MBC). Methods: Between November 2016 to January 2019, 408 patients underwent either unilateral or bilateral TKA at ten centers across India. Patients with primary end-stage osteoarthritis (OA) or inflammatory arthritis were included whereas, revision TKA patients were excluded from the study. Primary endpoints were 3-year implant survivorship and revision rates, with secondary endpoints including range of motion (ROM), Knee Society Score (KSS), and quality of life (QoL) assessed through WOMAC and SF-36 at 6 weeks, 6 months, 1- and 3 years. Results: The study comprised 242 unilateral and 166 bilateral TKA patients, with an average age of 65.13 ± 8.35 and 64.34 ± 7.25 years, respectively. Both groups exhibited a mean body mass index of 27.13 ± 4.73 kg/m2 and 27.80 ± 4.41 kg/m2. Female patients dominated the groups: 78.1 % and 86.75 % respectively, and the primary diagnosis was OA: 97.11 % and 96.39 %, respectively. Significant ROM improvement was observed in both groups (p < 0.001). Notable improvement was seen from baseline in mean clinical KSS (bilateral: 33.28 ± 15.84 to 91.06 ± 8.52, p < 0.001; unilateral: 31.26 ± 15.7 to 92.43 ± 8.07) and functional KSS (bilateral: 30.17 ± 21.19 to 98.50 ± 4.08, p < 0.001; unilateral: 26.59 ± 21.25 to 98.41 ± 4.33, p < 0.001) at 3 years. Baseline WOMAC scores among both the groups showed higher pre-operative values (25.78 and 23.91) which significantly lowered for pain (scores: 1.16 and 1.46), stiffness (scores: 0.53 and 0.68) and physical function (scores: 2.89 and 3.1) at 3 years indicating improved QoL. Similar significant trend was noted for SF-36 assessment (p < 0.001) in both the groups. Conclusion: This PMS study concluded that unilateral and bilateral TKA using MBC yielded good outcomes and there was a significant improvement in ROM, KSS scores and QoL in patients with osteoarthritis-associated joint degeneration.